Comparative study of specific stability isolates and strains Brucella Abortus - Орлов, С. М. (Scientific Progress & Innovations, 2012)
Investigated the stability of the species (cultural and morphological, antigenic properties) 6 isolates, dedicated in different stages of eradication of brucellosis in Ukraine, and 3 reference strains of Brucella abortus. In sowing on nutrient medium all selected culture after prolonged storage in the lyophilized state at a temperature (4±1) о C for 20–50 years were found alive. In the process of cloning revealed that isolates and reference strains retained the characteristic types of species of brucella in the S- or RS-forms.